The efficacy of parasacral transcutaneous electrical nerve stimulation for the treatment of overactive bladder in children: a systematic review and meta-analysis - Cheng, Zhuoqi; Chai, Yumeng; Zhou, Zhongbao; Zhang, Yong (Frontiers in Pediatrics, 2025)
AimDespite the presence of published evidence in recent decades suggesting an improvement in overactive bladder (OAB) with the utilization of parasacral transcutaneous electrical nerve stimulation (PTENS), there is currently a lack of consensus guidelines for therapy. We conducted a meta-analysis to assess the impact of PTENS on children with OAB.MethodsA search was carried out using EMBASE, PubMed, and the Cochrane Controlled Register of Trials to find eligible randomized controlled trials (RCTs) published up to 1 May 2023. From the literature review, eight RCTs (351 participants) comparing PTENS and other treatments (standard urotherapy/anticholinergics/biofeedback/placebo stimulation) were considered.ResultsThe overall complete response rate with PTENS was 1.90 times that of children undergoing other treatment (relative risk 1.90, 95% confidence interval 1.45–2.49). No significant differences were observed in the mean dysfunctional voiding score system (p = 0.26), mean maximum voided volume (p = 0.79), average voided volume (p = 0.94), voiding frequency (p = 0.31), or reduction in the number of children with incontinence episodes (p = 0.81). However, regarding the reduction of children with constipation, the PTENS group demonstrated a better effect compared with the control groups (p = 0.01).ConclusionsIn summary, PTENS has demonstrated better response rates and fewer side effects compared to conventional first-line treatments, such as standard urotherapy and antimuscarinic drugs. Clinicians should consider individual circumstances when treating children with OAB. However, it is important to note that the findings of this study are limited by the small sample size and imperfect outcomes. Further high-quality RCTs are needed to establish the most effective treatment protocol.